EXPLORING GUEST SATISFACTION IN HOTELS DURING THE COVID-19 PANDEMIC USING A TEXT MINING TECHNIQUE - Čelić, Irena; Seočanac, Marijana; Milašinović, Marko (Ekonomija - teorija i praksa, 2021)
The coronavirus pandemic has a major impact on the global hotel industry. Hygiene, cleanliness, and safety have become crucial components in any hotel’s recovery plan during the pandemic. Based on reviews from Booking.com, this paper examines the satisfaction of domestic guests in hotels in Vrnjačka Banja during the coronavirus pandemic. Additionally, by using the „Clean & Safe“ certificate as a criterion for hotel classification, this paper seeks to discover whether there is any difference in the satisfaction of domestic guests depending on whether the facility has been certified in accordance with international quality standards as adequately prepared for virus control. Using a text mining approach, the components that led to guests’ satisfaction or dissatisfaction were discovered and visualized with a word cloud. A sample of 206 reviews revealed that domestic guests are generally very satisfied with the hotels they stayed in during the pandemic. A slight difference in the components that affected guests’ satisfaction, i.e., dissatisfaction, was noticed among the hotels that were certified (or not certified) as safe facilities for performing tourism activities. This paper provides a valuable insight for hotel managers to help them improve guest satisfaction during the coronavirus pandemic.